Managing Distress Using Mobile Prescriptions of Psychological Pills: A First 6-Month Effectiveness Study of the PsyPills App - David, Oana A.; David, Daniel (Frontiers in Psychiatry, 2019)
Background: Although numerous mental health apps are commercially available, only few of them have been tested in terms of their effects in promoting mental well-being. PsyPills is the first app using the principles of a specific form of CBT (Rational Emotive Behavior Therapy; REBT) and grounded in the emotion-regulation research, able to function as stand-alone, interactive, and personalized mobile based intervention for offering immediate relief from stress. Objective: In this paper, we describe the newly developed PsyPills app for stress management and present the data obtained at six months after release for investigating its effectiveness in helping users manage their stress. Methods: Participants were 115 users aged 15-79 years old (M=39.01, SD=13.49) who accessed the app during the first 6 months after being launched and thus were included in our study. Stress and specific cognitive processes were registered using visual analogue scale type measures. Results: We found that most of the users accessed the app with the purpose of searching anxiety relief and reported most often work-related distress. 74 of the users have accessed PsyPills between 1 and 11 times (M=2.68, SD=2.59), and they received 258 psychological prescriptions. Results obtained show that the PsyPills app can be effective in terms of reducing the frequency of dysfunctional emotions, such that significantly more users reported feeling functional emotions after accessing it and reading its personalized prescription than those reporting not being able to change it (χ²(1, N=52)=52.00 p<.001). Using reminders of the psychological pill at specific times during the day made the PsyPills app more effective. Conclusions: Based on initial data on its first 6-month usage, the PsyPills app has proven to be promising in terms of offering relief for stress but future studies need to use golden standard design and investigate its efficacy as adjunctive intervention.